Alkaline-earth elements of scalp hair and presence of hypertension in housewives: A perspective of chronic effect. (August 2017) - Wang, Bin; Yan, Lailai; Sun, Ying; Yan, Jingjing; Lu, Qun; Zhang, Jingxu; Li, Zhiwen
Abstract: The relationship between population intakes of alkaline-earth elements (AEEs) and hypertension risk remains under discussion. Hair AEE concentrations can indicate their intake levels into human body. Thus, we aimed to investigate an association of hair AEE concentrations with hypertension risk, and the potential effect of dietary habit on this association. We recruited 398 housewives [163 subjects with hypertension (case group) and 235 subjects without hypertension (control group)] in Shanxi Province of north China. The scalp hair grown in the recent 2 years of each subject was collected and analyzed for the four concerned AEEs [i.e. calcium (Ca), magnesium (Mg), strontium (Sr), and barium (Ba)]. Our study results revealed that median concentrations (μg/g hair) of hair AEEs in the case group were systematically lower than those in control group [i.e. 701 vs. 1271 of Ca, 55.2 vs. 88.3 of Mg, 4.60 vs. 10.4 of Sr, and 1.02 vs. 1.68 of Ba]. Lower levels of the four individual AEEs of hair were associated with an increased presence of hypertension, respectively. Moreover, hair AEE concentrations were all positively correlated with the ingestion frequencies of meat, eggs, fresh vegetables, and fruits, while negatively with that of salted vegetables. A high ingestion frequency of fresh vegetables was associated with a lower prevalence of hypertension with or without adjusting confounders, while salted vegetables revealed a reverse tend. It was concluded that low hair AEEs, as markers of their long-term dietary intake, were associated with the presence of hypertension in a rural Chinese women. Highlights: Ca, Mg, Sr & Ba are typical alkaline earth elements (AEEs) related to human health. We aimed to investigate an association of hair AEEs with presence of hypertension. Our cross-sectional study was conducted among housewives in Shanxi Province, China. Lower levels of hair AEEs were associated with an increased hypertension presence. Hair AEEs concentrations were correlated with dietary habit of housewives.